Pressure ulcer (risk) assessment: Recommendations to improve nursing practice - Garcez Sardo, Pedro Miguel (2018)
Pressure ulcer (risk) assessment is complex and multifactorial. National and international guidelines give orientations about pressure ulcer (PU) management and provide important recommendations. However, it’s necessary to know our reality in order to improve Evidence-Based Nursing. The main aim of this study was to provide some recommendations to improve clinical practice, clinical research, clinical management and continuous education on PU domain. The study was designed as a retrospective cohort analysis of electronic health record database from adult patients admitted to general wards in a Portuguese hospital during one year. The study had a sample of 8147 participants where 34.4% had “high risk” of PU development at the #rst PU risk assessment, 7.9% had (at least) one PU at the #rst skin and tissue assessment and 3.4% developed (at least) one PU during the length of inpatient stay. (Im)“mobility” was the major risk factor assessed through Braden Scale for PU development. The systematic PU risk assessment: is sensitive to patient clinical changes; should be performed since the hospital admission; and should be used in combination with nursing clinical judgement. The systematic skin and tissue assessment: identi#es early changes in skin and tissue condition; should be performed since the hospital admission; and should identify wounds of di$erent aetiologies. The PU assessment could be improved with the implementation of a validated tool in order to standardised data record, to monitor PU/wounds characteristics and their evolution.